Term-creation strategies used by Ndebele translators in Zimbabwe in the health sector: A corpus-based approach - Ndhlovu, Ketiwe (Stellenbosch Papers in Linguistics Plus, 2014)
In the scientific arena, many African languages face the challenge of a lack of terminology. That is, translators who translate from developed Western languages into African languages often encounter a lack of adequate terminology in their efforts to communicate between these languages. The health sector seems particularly problematic, since it involves a continuously evolving discipline that requires continuously evolving terminology creation. This article explores strategies used by Ndebele translators to create terms in the health sector. In order to identify specialised terms and their Ndebele translations, the English-Ndebele Parallel Corpus (ENPC), created by Ndhlovu (2012), was interrogated. Borrowing in the form of pure loaning acronyms and abbreviations, pure loaning words, indigenisation, pure loan words preceded by an explanation, and abbreviations preceded by an explanation were identified as the most commonly used strategies in Ndebele medical translations, followed by semantic shift using borrowed synonyms and paraphrasing. The least used strategies were paraphrased acronyms and abbreviations, coinage and compounding. In the article, it was noted that in order to fully understand the strategies employed by Ndebele translators from a corpus-based approach using ParaConc, there is a need to have knowledge of prefixal elements of Ndebele terms. This is because searching for the head word outside its prefixal elements brings about incomplete results, thereby presenting an incomplete picture of the strategies under study.